2008
DOI: 10.1007/s10787-007-1578-0
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal disorders induced by non-steroidal anti-inflammatory drugs

Abstract: Patients 65 years old and over with continuous NSAIDs use had asymptomatic ulcers, and patients 80 years old and over had hemorrhagic ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…NSAIDs block prostaglandin synthesis by inhibiting cyclooxygenases, leading to an erosion and then ulceration of the mucosal layer. These ulcers are most often seen in the gastric and duodenal region ( 30 ), although some studies have shown long-term NSAID users to have ileocecal ulceration as well ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSAIDs block prostaglandin synthesis by inhibiting cyclooxygenases, leading to an erosion and then ulceration of the mucosal layer. These ulcers are most often seen in the gastric and duodenal region ( 30 ), although some studies have shown long-term NSAID users to have ileocecal ulceration as well ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…HUFAs containing [26][27][28][29][30][31][32] carbons that are components of the sphingolipids present in spermatozoa ( 14 ). The exact function of these very long chain HUFAs in spermatogenesis is yet to be elucidated.…”
mentioning
confidence: 99%
“…The gastrointestinal and renal side effects are important untoward clinical events associated with the use of both selective and non-selective COX inhibitors (Gambaro and Perazella 2003;Sandhu and Heyneman 2004;Chiba et al 2008). Recently, it has been observed that co-administration of NSAIDs such as ibuprofen, meloxicam and celecoxib with paracetamol, most commonly used combination therapy clinically, produced synergistic nephrotoxicity and gastrotoxicity in rats (Kumar et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although, non-steroidal anti-inflammatory drugs (NSAIDs) are the mainstay of pharmacological therapy in the management of RA, their use is often associated with gastrointestinal ulcers and bleeding, in about 15-30% of the chronic users (James and Hawkey 2003;Kean and Buchanan 2005;Chiba et al 2008). Ibuprofen, a prototype of propionic acid derivative of NSAIDs group, is an effective and widely used drug to treat moderate to severe inflammatory conditions at the daily dose of 800-1,200 mg, including RA and osteoarthritis, since, it is preferentially accumulated and is retained in inflamed arthritic joints, where analgesic and antiinflammatory effects are required (Kilo et al 1995;Kean et al 1999;Rainsford 2009).…”
Section: Introductionmentioning
confidence: 99%
“…100 While NSAIDs are usually well tolerated for short periods of time, chronic use can lead to gastrointestinal complications (eg, ulcer formation, perforations, and bleeding), and renal toxicity. 101,102 Gene-based dosing for NSAIDs aimed at reducing the occurrence of ADRs is hindered by differing metabolic rates among various NSAIDs and the involvement of additional metabolizing enzymes (eg, CYP2C8). Individuals carrying the gene variants CYP2C8*3 (rs11572080; rs10509681), CYP2C9*2 (rs1799853) or CYP2C9*3 (rs1057910) show increased risk of developing acute gastrointestinal bleeding with NSAID therapy.…”
Section: Nsaidsmentioning
confidence: 99%